Business Sector Engagement in Pentahelix Colaboration for Stunting Reduction: A Qualitative Study in Jember Regency - Prasetyowati, Irma; Wahyu Ningtyias, Farida; Ratnawati, Leersia Yusi; Bumi, Candra; Nurika, Globila; Haryanik, Meilinda Alya' Putri (Universitas Airlangga, 2026)
Background: Stunting is a persistent public health issue in Indonesia, with long-term effects on children's physical and cognitive development. In 2023, Jember Regency recorded the highest stunting prevalence in East Java at 29.7%. Objective: To examine the role of the business sector in efforts to reduce stunting in Jember within the Pentahelix collaboration model. Methods: This study employed a qualitative case study design using in-depth interviews and focus group discussions. Data were analyzed using Buse, Mays, and Walt’s policy implementation framework (Buse, Mays, & Walt, 2012), which focuses on context, content, process, and actors. This framework was chosen because it provides a comprehensive approach to understanding how policies are implemented through multi-actor collaboration, making it relevant for analyzing the Pentahelix model in stunting reduction efforts. Results: Findings indicate that businesses contribute significantly through Corporate Social Responsibility (CSR) initiatives, including Posyandu activities, nutrition support, and economic empowerment programs for mothers in areas with high rates of stunting. Coordination with health offices is based on local data, ensuring interventions are targeted and effective. The CSR Forum serves as a platform for aligning business efforts with public health goals. Businesses are also engaged in monitoring and evaluation through regular reporting from health facilities. Conclusion: Active engagement of the business sector through CSR initiatives strengthens stunting reduction efforts by supporting government and community programs. Integrating business participation into health promotion practice enhances sustainability, coordination, and long-term impact on child health and nutrition.